Pharmacokinetics and tissue penetration of Ro 23-6240, a new trifluoroquinolone. - Wise, R (1987)
A 400-mg dose of the trifluorinated quinolone Ro 23-6240 was administered orally to each of six healthy male volunteers, after which the concentrations of this agent in serum and cantharidin-induced inflammatory fluid were measured. Absorption was rapid, with a mean peak level in serum of 6.1 micrograms/ml, which was attained 0.71 h after administration. The elimination half-life in serum was 11.95 h. The agent penetrated the inflammatory fluid rapidly; the percent penetration was 89.7%. Urinary recovery of Ro 23-6240 was 58.6% by 72 h.